Circulating tumor stem cells and glioblastoma: A review. (March 2019) - van Schaijik, Bede; Wickremesekera, Agadha C.; Mantamadiotis, Theo; Kaye, Andrew H.; Tan, Swee T.; Stylli, Stanley S.; Itinteang, Tinte
Highlights: Cancer stem cells (CSCs) drives tumorigenesis. The aggressiveness of glioblastoma has been attributed to the presence of CSCs. Circulating tumor stem cells (CTSCs) can be derived from CSCs. An initial EMT followed by MET by these primitive cells underscore metastasis. Abstract: Glioblastoma (GB) is the most aggressive primary brain tumor in adults. The aggressive nature of GB has been attributed to the presence of cancer stem cells (CSCs) which drive tumorigenesis and are thought to be the root cause of the disease. Circulating tumor stem cells (CTSCs), which can be derived from CSCs, have been identified in numerous types of cancer including GB, have been proposed to contribute to local and distant recurrence. There are many technical difficulties in studying CTSCs, therefore there is a significant gap in the literature pertaining to how they arise and function, and how the understanding of the biology of CTSCs could elucidate the underlying cause of local recurrence and metastasis. An initial epithelial-to-mesenchymal transition (EMT) followed by mesenchymal-to-epithelial transition involving these primitive cells appear to be the critical processes underpinning metastasis. This review focuses on the association between CSCs undergoing EMT to become CTSCs, and how this could arise from the CSC subpopulation in GB, and contribute to the understanding of the pathogenesis and treatment.